Community as curriculum: Dewey’s theory of inquiry in the context of an urban agriculture project - Won, Mihye; Bruce, Bertram C (Springer Nature, 2021)
Urban agriculture programs are recognized as an effective way to bring students’ cultural funds of knowledge into their school-based science learning, and in turn, to use the school-based learning to effect changes in the community. However, despite their potential to engage students in meaningful learning and to break the boundaries between school and community, many such programs are poorly integrated into the school-based science curriculum. In this study, we describe an urban agriculture project that was systematically integrated into high school science teaching and supported by the whole school community, later contributing to community action in the neighbourhood. Employing John Dewey’s theory of inquiry as the analytical framework, we discuss the educational implications of the urban agriculture project and examine the goals of education and the value of the urban agriculture program, in terms of the growth of students and community.